Oral lichen planus: A look from diagnosis to treatment. - Pablo Córdova; Aida Rubio; Paula Echeverría (Universidad de Concepción., 2014)
Oral lichen planus (OLP) is a chronic mucocutaneous disease of unknown etiology. Its pathogenesis is multifactorial and it may affect the oral mucosa, skin and other mucous membranes. Diagnosis is based on clinic and histopathology; direct immunofluorescence techniques can also be of use. It affects about one to two percent of the population, mainly women between the fifth and sixth decades of life. In the mouth, the most affected area is the buccal mucosa, followed by the gums, tongue and/or palate. Its three most representative clinical forms are reticular, erythematous and erosive; evolution depends on the type it is. Lesion treatment is determined by the clinical form and, since no fully effective treatment has been found yet, it is directed towards controlling the disease. The treatment of choice involves topical or systemic corticosteroids, but other drugs may also be used.The aim of this paper is to gather current and relevant information about oral lichen planus: its pathogenesis, diagnosis, treatment and management.